A Cross‐Linkable Donor Polymer as the Underlying Layer to Tune the Active Layer Morphology of Polymer Solar Cells. (24th November 2015) - Meng, Bin; Wang, Zaiyu; Ma, Wei; Xie, Zhiyuan; Liu, Jun; Wang, Lixiang
Abstract : For polymer solar cells (PSCs) with conventional configuration, the vertical composition profile of donor:acceptor in active layer is detrimental for charge carrier transporting/collection and leads to decreased device performance. A cross‐linkable donor polymer as the underlying morphology‐inducing layer (MIL) to tune the vertical composition distribution of donor:acceptor in the active layer for improved PSC device performance is reported. With poly(thieno[3, 4‐ b ]‐thiophene/benzodithiophene):[6, 6]‐phenyl C71 ‐butyric acid methyl ester (PTB7:PC71 BM) as the active layer, the MIL material, PTB7‐TV, is developed by attaching cross‐linkable vinyl groups to the side chain of PTB7. PSC device withPTB7‐TV layer exhibits a power conversion efficiency (PCE) of 8.55% and short‐circuit current density ( J SC ) of 15.75 mA cm −2, in comparison to PCE of 7.41% and J SC of 13.73 mA cm −2 of the controlled device. The enhanced device performance is ascribed to the much improved vertical composition profile and reduced phase separation domain size in the active layer. These results demonstrate that cross‐linked MIL is an effective strategy to improve photovoltaic performance of conventional PSC devices. Abstract : A cross‐linkable donor polymer is developed and used as the underlying layer to improve the vertical composition distribution of donor:acceptor in the active layer of polymer solar cells (PSCs). With the improvement, the regular PSC device based on PTB7:PC71 BM active layer exhibits power conversion efficiency increase from 7.41% to 8.55%.